To what extent do welfare states compensate for the cost of children? A hypothetical household approach to policy evaluations. - Tess Penne; Tine Hufkens; Tim Goedemé; Bérénice Storms (European Commission, Joint Research Centre (JRC), 2018)
In order to alleviate child poverty, contemporary European welfare states have shifted their focus increasingly towards child-centred investment strategies. However, studies assessing the generosity of welfare states to families with children focus mainly on the role of cash benefit packages, or on government expenditure, disregarding the actual costs families face when accessing essential goods and services. This paper takes a hypothetical household approach to family policy evaluations and aims at contributing to existing studies by: (1) empirically assessing the needs and costs of children across welfare states by making use of cross-nationally comparable reference budgets, while taking into account publicly-provided or subsidized services, (2) simulating the taxes and cash benefits that households with children receive through the tax-benefit system, by making use of the new Hypothetical Household Tool (HHoT), and, (3) combining both types of information in order to compare the essential out-of-pocket costs of children between 6 and 18 years old with the simulated cash benefit packages. The paper focuses on six European welfare states: Belgium, Finland, Greece, Hungary, Italy and Spain. We propose a new indicator that can be used to assess welfare state generosity to families with children: the child cost compensation indicator. The indicator allows cross-country comparison on the role of taxes and social benefits in the EU. By making use of this indicator, we show that, even though with important cross-national variation, the out-of-pocket cost of children is generally compensated to a small extent through cash policies. Although support for families is higher at the lower end of the income distribution, for households living on a low gross wage, the income of a family with children is less adequate compared to a similar childless family, and is in many cases insufficient to participate adequately in society.
Keywords: 330; welfare state generosity; cost of children; in-kind benefits; reference budgets; hypothetical household simulations